RELACIÓN ENTRE CONDUCTA ALIMENTARIA Y POTENCIAL CARIOGÉNICO EN LA PRIMERA INFANCIA. UNA REVISIÓN - Guanoluisa-Barragán, Ninoshka Darling (2025)
Introduction: Feeding behavior encompasses a set of individual and group actions related to food use and consumption. Analyzing these dietary patterns serves a crucial tool for obtaining precise and relevant data to assess the dental and nutritional status of a population. We aimed to examine the relationship between dietary behaviors and their cariogenic potential in early childhood through a narrative review of scientific literature published among 2017 and 2024. Materials and Methods: Medline, LILACS, and ScienceDirect databases were searched using Boolean operators to combine search terms and filter results by meta-analyses, systematic reviews, observational studies, case studies, randomized controlled trials, and cross-sectional studies. Of the 106 articles retrieved, we included 9, because those met the inclusion and exclusion criteria. Results: The results highlighted the need to promote proper nutrition from early life to prevent dental diseases in children. Additionally, we emphasize the importance of fostering oral health care, including correct brushing techniques, among both parents and caregivers. Conclusion: We concluded that oral health education is a cornerstone for addressing this significant public health issue.